Refuse and the formation of middens - Needham, Stuart
The prodigious quantities of refuse recovered from excavations at Runnymede Bridge, Berkshire, England Ñ and at other late prehistoric British sites Ñ highlight those archaeological entities we call 'rubbish' and 'middens'. What is a 'midden'? General thoughts on an archaeology of refuse are applied to the specific case of these 1st-millennium BC sites in southern England in an attempt to comprehend their origin and scale in terms of the period's social geography.